Community-Based Learning as a Pathway to Fostering Student Civic Engagement - Pradana, Yudha; Darmawan, Cecep; Rahmat, Rahmat; Anggraeni, Leni; Syaura Binti Shariffuddin, Naya (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This research will reveal how the Village Community Empowerment Program/Program Pemberdayaan Masyarakat Desa (P2MD) is implemented as community-based learning to foster civic engagement. Community-based learning creates opportunities for real learning experiences for students and builds connections between higher education institutions and the community to address societal problems and achieve the public good. Method: This study is qualitative and employs a phenomenological methodology. Data collection techniques include interviews and documentation studies. The participants are students from the Multimedia Student Association of the State Polytechnic of Creative Media, implementing P2MD in 2023. Results: The research results reflect students' engagement as citizens in addressing societal issues to achieve the public good, focusing on the waste bank management program. This program also promotes community empowerment in a participatory manner. Students' citizenship attributes include altruism, leadership, communication, problem-solving, creativity, and collaboration. Novelty: This study underlines the importance of critical reflection as an integral part of the learning process. By exploring the experiences of students involved in community activities, this study provides new insights into how community-based learning can develop critical thinking skills and effective communication skills.